Does Political Partisanship Cross Borders? Evidence from International Capital Flows - Elisabeth Kempf; Mancy Luo; Larissa Schafer; Margarita Tsoutsoura (University of Chicago Booth School of Business, Stigler Center for the Study of the Economy and the State, 2022)
Does partisan perception shape the flow of international capital? We provide evidence from two settings, syndicated corporate loans and equity mutual funds, to show ideological alignment with foreign governments affects the cross-border capital allocation by U.S. institutional investors. Our empirical strategy ensures direct economic effects of foreign elections or government ties between countries are not driving the result. Ideological alignment with foreign countries may also affect capital allocation of non-U.S. investors and can explain patterns in bilateral investment. Combined, our findings imply partisan perception is a global phenomenon and its economic effects transcend national borders.
Keywords: 330